An industrial-grade Nicotiana benthamiana line for the production of glycoproteins carrying fucose-free galactosylated N-glycans - Kogelmann, Benjamin; Melnik, Stanislav; Keshvari, Tahereh; Bogner, Michaela; Lavoie, Pierre Olivier; D`Aoust, Marc Andre; Hermle, Antonia; Lux, Anja; Strasser, Richard; Stöger, Eva; Steinkellner, Herta (New Biotechnology, 2025)
β1,4-galactosylation is a typical human N-glycan formation with functional impact on proteins, particularly known for IgGs. Therefore, the expression of recombinant proteins with controlled galactosylation is an important quality parameter in the biotech industry. Here we describe the establishment of a plant-based expression platform for the manufacturing of recombinant proteins carrying β1,4-galactosylated N-glycans. A genome-edited Nicotiana benthamiana glycosylation mutant (NbXF-KO) that synthesizes conserved eukaryotic GnGn structures served as a template for further elongation toward β1,4-galactosylated N-glycans. A hybrid β1,4-galactosyltransferase gene that targets the enzyme to a post-Golgi compartment was introduced into the NbXF-KO genome without any additional foreign DNA sequence. The efficient generation of “marker-free” transgenic lines (NbXF-KOGal) was achieved by using a dual-vector strategy and visual screening procedures. Of note, a monoclonal antibody expressed in NbXF-KOGal exhibited up to 70 % galactosylated, fucose/xylose-free N-glycans, in a batch-to-batch consistent manner. Given recent findings attributing anti-inflammatory activities to nonfucosylated, galactosylated IgG, our results gain new significance.
CRIS-Team Scopus Importer:2024-12-13
Keywords: Galactosylated fucose-free N-glycans; N-glycan engineering; Nicotiana benthamiana; Recombinant glycoproteins; β1; 4-galactosylation